Dukungan Sosial dan Self-Regulated Online Learning Belajar Matematika Siswa SMA di Masa Pandemi - Aina P. Khairani; Sumedi P. Nugraha (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. There are various obstacles occurring during the online learning process, one of which is in mathematics. To cope with these obstacles, self-regulated online learning (SROL) skills and good social support are deemed necessary. This study aimed to determine a relationship between social support and students' SROL in mathematics as seen from the social support sources in MIPA class students in SMA N “X” Kendal. The measuring instrument used in this study was the SROL scale from Arbiyah and Triatmoko (2016) with 24 items and the SSQC Gordon scale (2011) with 50 items. Total participants of this study are 220 MIPA class students in SMA N “X” Kendal from X to XII grade. Data analysis in this study used regression analysis. The results of data analysis showed the value of F = 8.416 with p value = < 0.001. These results indicated that social support could simultaneously predict the SROL of students in SMAN